A new semiparametric approach to analysing conditional income distributions - Alexander Sohn; Nadja Klein; Thomas Kneib (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
In this paper we explore the application of Generalised Additive Models of Location, Scale and Shape for the analysis of conditional income distributions in Germany following the reunification. We find that conditional income distributions can generally be modelled using the three parameter Dagum distribution and our results hint at an even more pronounced effect of skill-biased technological change than can be observed by standard mean regression.
Keywords: C13; C21; D31; J31; 330